Mineralogical features and petrogenetic significance of the clinopyroxene and hornblende of the Wuhaolai mafic complex in northern North China Craton, Inner Mongolia - Chen Wang; Liu Jianchao; zhang Haidong; Ge Jiakun; Xi Zhixuan; Wang Haoran (Earth Sciences Research Journal)
The Wuhaolai mafic complex is located in the north margin of the North China Craton (NCC), Inner Mongolia. To discuss the mineralogical features, magma evolution process, and tectonic setting of the complex, we analyzed the geochemical compositions of clinopyroxene and hornblende using an electron probe. The results revealed that the parental magma of this complex belonged to the intraplate alkaline basalt series. The normal zoning texture and the relation between Mg# and FeO, Al2O3, CaO, Na2O, SiO2 and Cr2O3 suggested that the clinopyroxenes of pyroxenite and gabbro crystallized from the same parental magma. The similar CaO content of clinopyroxenes indicated that the parental magma of the Wuhaolai complex may have suffered crustal contamination. Furthermore, the characteristics of hornblende demonstrated that the magma source was modified by fluids derived from subducted slab. Based on the value of Kdcpx (0.23–0.27), the equilibrium melt with clinopyroxene exhibited a relatively low Mg# (43–53), indicating that the parental magma was derived from the lithospheric mantle and underwent crystal fractionation. The gabbro crystallization temperature and pressure was found to be lower than that of pyroxenite, indicating that gabbro was formed at a lower depth than that of pyroxenite. Combining the tectonic setting discrimination diagram of clinopyroxene with the results of previous studies on the late Paleozoic intrusions near the research area, we proposed that the Wuhaolai complex was formed in an intraplate environment. The magma source was modified by fluids derived from the subducted slab during the subduction of the Paleo-Asian Ocean (PAO). After the PAO closure, the parental magma of the Wuhaolai complex was produced by the partial melting of the enriched lithospheric mantle